BRAF Mutations in Patients with Non-Small Cell Lung Cancer: A Systematic Review and Meta-Analysis - Chen, Dong (Public Library of Science, 2014)
BACKGROUND: BRAF mutations have been well described in non-small cell lung cancer (NSCLC) for several years, but the clinical features of patients harboring BRAF mutations are still not well described. We performed a meta-analysis to identify common clinical features in NSCLC patients carrying BRAF mutations. METHODS: We identified clinical studies that examined the association between BRAF mutations and features of NSCLC within PubMed, Embase and ISI Science Citation Index database up to October 2013. The effect size of clinical features was estimated by odds ratios (ORs) with 95% confidence interval (CI) for each study, using a fixed-effects or random-effects model. RESULTS: Ten studies with a total of 5599 NSCLC patients were included. There was a 3% (170/5599) BRAF mutation rate. BRAF mutations in NSCLC were significantly associated with adenocarcinomas (ADCs) (compared with non-ADCs, OR = 4.96, 95%CI = 2.29–10.75). There were no significant differences in gender, smoking and stage in patients with and without BRAF mutations. The BRAF (V600E) mutation was more frequent in women than non-BRAF (V600E) mutations (OR = 0.27, 95%CI = 0.12–0.59), and was closely related to never smokers (OR = 0.14, 95%CI = 0.05–0.42). CONCLUSIONS: These findings have important implications for the prediction of the NSCLC sub-types more accurately combined with other genetic changes.